Initial Sofa Score and Mortality of Sepsis Patients in the Intensive Care Unit of Haji Adam Malik Hospital Medan: Does It Correlate? - Hanif, Raisa Syifa; Hamdi, Tasrif; Kadri, Alfansuri; Megawati, Eka Roina (Faculty of Medicine-Universitas Airlangga, 2024)
Introduction: Sepsis is a life-threatening organ dysfunction or failure that is the primary cause of death in infectious disease. the Sepsis-3 Task Force recommends The Sequential (Sepsis-Related) Organ Failure Assessment (SOFA) Score as a means of Sepsis identification. Objective: To determine the correlation between sepsis patients’ deaths in the intensive care unit (ICU) of Haji Adam Malik Hospital Medan and their initial SOFA score. Methods: This study uses a cross-sectional study design and an observational analytical investigation. The sample for this study was sepsis patients who were treated in the ICU of Haji Adam Malik Hospital Medan in 2021-2022, and they were selected using the purposive sampling method. After calculating the Slovin formula, 61 samples are required. The researchers obtained the data from patient medical records. The analyses used are univariate and bivariate, with the Independent-T test and Fisher’s exact. Results: From 71 patients, there were 36 patients (50.7%) in the age group of 46-65 years old; 39 patients (54.9%) were male; 50 patients (70.4%) had comorbidities; and 50 patients (70.4%) had non-surgical disease. The average initial SOFA score was 9.89 ± 3.95, with mortality for sepsis patients in the ICU of 74.6%. The findings of the statistical analysis indicated a substantial difference (p<0.001) in the SOFA scores of those who survived and those who did not, as well as a significant correlation (p<0.001) between the initial SOFA score and mortality. Conclusion: There is a correlation between initial SOFA score and the mortality of sepsis patients in the ICU of Haji Adam Malik Hospital.